Students’ Perception Toward the Efl Lecturer’s Code-Switching in PGSD’S English Classroom - Fatsah, Hasanuddin; Purnama, Indah (Jurnal Pedagogi dan Pembelajaran, 2022)
Primary school is the foundation of formal schooling which can affect the aftermath. This study analyses the perception of Primary school teacher education or PGSD student toward the code-switching made by EFL lecturers in English classrooms and the benefits for them in learning English. This study using a mixed-method, the eligible participant received questionnaire and semi-structured interview protocols were carried out in the Indonesian language. The data from the questionnaire was analyzed by Likert scale and the semi-structured interview was analyzed by thematic analysis. The findings showed that first, students have a positive perception toward the code-switching done by the lecturer in English classroom; second, benefits that the students get from code-switching in English classroom are increase the level of English vocabulary capacity mastery, help in understanding lessons, learn the English language better, help understanding course assignments, improves English speaking skill, improves English listening skill. As the conclusion, the code-switching used for teaching English in the classroom had given great impact on PGSD students which is most of the students showed a positive perception toward the used of Code-switching.